تحقيق حول فعالية أدوات الترجمة الالية في تحسين مهارات فهم القراءة بين المتعلمين اللغة الانجليزية - الشوشان مها عبدالله صايغ (مجلة الاصالة, 2026)
This study investigates the effectiveness of machine translation tools in improving reading comprehension skills among English language students. With the increasing availability of digital translation technologies students frequently rely on machine translation to support their understanding of English texts. This research aims to examine whether the use of such tools positively influences learners’ reading comprehension and overall language learning experience. A quantitative research approach was employed, involving reading comprehension tests and questionnaires administered to English language students. Quantitative data were analyzed to measure changes in comprehension performance, The findings indicate that machine translation tools can significantly enhance students’ understanding of reading materials, particularly for lower-proficiency ones, by facilitating vocabulary recognition and text interpretation. However, overreliance on these tools may limit the development of independent reading strategies. The study concludes that when used appropriately, machine translation tools can serve as effective supplementary resources in English language learning. Implications for educators and recommendations for integrating machine translation tools into reading instruction are discussed.